EVALUASI PEMANFAATAN KOLEKSI PERPUSTAKAAN DI UPT. PERPUSTAKAAN PUSAT UNIVERSITAS MAHASARASWATI DENPASAR - Meitriyanti, Ni Putu Heny; Ginting, Richard Togaranta; Kastawa, Made (Jurnal Ilmiah D3 Perpustakaan, 2019)
ABSTRACT The purpose of this study was to find out the use of colleections available at Central Library of Mahasaraswati University which are expected to be able to support learning and research activities. The objectt of this research is the collection available at the Central Library of Mahasaraswati University, Denpasar. The ppopulation of this research is all students who are members of the Central Library of Mahasaraswati University Denpasar. The number of samples was 89 respondents using the Slovin formula. Time of study in April 2016. Keywords: utilization of collections, library collections, college libraries